Morphological study of Gelasinospora from dung and antagonistic effect against plant pathogenic fungi in vitro - Piasai, Onuma; Sudsanguan, Manorat (Agriculture and Natural Resources, 2018)
Animal dung samples were collected from Surin and Suphan Buri provinces, Thailand. The alcohol treatment technique was used for fungal isolation. Identification of the genus Gelasinospora was based on morphological characteristics of ascomata, asci and ascospore ornamentation when grown on potato dextrose agar. Microscopic features were examined under stereo and compound microscopes and ascospores were observed using a scanning electron microscope. Four species of Gelasinospora were recorded: G. calospora, G. hippopotama, G. indica and G. stellata. The generic diagnostic description of each species was recorded. The species G. hippopotama and G. stellata, which were isolated from cow and buffalo dung are new records for Thailand. The in vitro antagonistic activity tests were conducted using isolates of each of the four species of Gelasinospora against seven genera of plant pathogenic fungi. All isolates of Gelasinospora inhibited 100% on the mycelial growth of Phytophthora palmivora and also inhibited more than 75% of the mycelial growth of Alternaria alternata, Colletotrichum capsici and Curvularia lunata. All isolates failed to inhibit the mycelial growth of Rhizoctonia oryzae and Sclerotium rolfsii, except for G. hippopotama KUFC6898, which inhibited 75.5% of the mycelial growth of R. oryzae.